Pengelolaan Lingkungan dan Kondisi Masyarakat Pada Wilayah Hilir Sungai - Suganda, Emirhadi; Yatmo, Yandi Andri; Atmodiwirjo, Paramita (UI Scholars Hub, 2009)
River by nature is a unity, but there is a tendency to separate river management based on administrative areas. River is also related to the community living in its surrounding area. This paper discusses watershed issues related to the management and community condition, especially within the framework of interrelationship between upstream and downstream areas. Department of Public Works as the institution was responsible for the national water resource management has proposed the idea of